Apogee a community-based mountain resort - Lu, Janine Victoria Ana U.
This study explores the possibility of employing community involvement in the Davao City Mountain Resort Project. Through interview with the local community and government, research on existing resorts with similar visions, and reviewing literature about the subject, this study aims to design a cultural mountainside resort in Mound Apo, which is the highest peak in the Philippines, that best foster community-based tourism. The result is a proactive design that has taken the input of the local community, considered its culture and context to come up with Apogee: A Community-Based Resort.